Strategi pelestarian naskah kuno di Indonesia dalam tinjauan literatur sistematis - Nurpratama, Muhammad Rifky (UPT Perpustakaan Universitas Islam Negeri Walisongo, 2025)
Purpose. This study aims to examine the preservation of ancient manuscripts in Indonesia through a systematic review of academic literature over the past decade. These manuscripts, which hold historical, cultural, and educational significance, face growing threats due to climate change, physical degradation, and limited public awareness. Methodology. Using a Systematic Literature Review (SLR) approach, this study analysed 30 peer-reviewed articles published between 2010 and 2023. Articles were selected from open-access databases (Google Scholar, ResearchGate, and Garuda) using specific inclusion and exclusion criteria. The PRISMA flow diagram guided the selection process, and thematic analysis was used to synthesize the findings. Results and discussion. Findings indicate that manuscript preservation in Indonesia follows two major approaches: physical conservation (e.g., fumigation, environmental control) and digital preservation (e.g., high-resolution scanning, metadata development). While digitalization enhances access and reduces handling-related damage, it is hindered by outdated file formats, limited infrastructure, lack of skilled personnel, and legal uncertainties. Community-based efforts, cultural values, and institutional collaborations (such as those in Rekso Pustaka and Ranggawarsita Museum) demonstrate practical and adaptive models for sustainable preservation. Conclusions. The study recommends integrating physical and digital methods in a balanced and context-sensitive strategy. It emphasizes the importance of strengthening institutional capacity, expanding professional training, encouraging local participation, and ensuring policy support to sustain long-term preservation efforts across diverse cultural settings.